2020
DOI: 10.20944/preprints202003.0353.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Search of Feasible Interventions for the Prevention and Cure of Novel Coronavirus Disease 2019<strong> </strong>

Abstract: COVID-19 (coronavirus disease 2019) is a public health emergency of international concern caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). As of this time, there is no known effective pharmaceutical, phytopharmaceutical or traditional medicine for cure or prevention of COVID-19, although it is urgently needed. In this review, based on the current understanding of the disease molecular mechanisms of novel Coronavirus SARS-CoV-2 and its closest relative SARS-CoV and other human Coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…It exhibits several pharmacologic properties, such as antioxidant, antiinflammatory, and antifibrotic properties. It is important to note that not all the analogs are the same, and their stability and efficacy are dose-dependent and related to a specific type [15][16][17].…”
Section: Curcumin (Curcuma Longa)mentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits several pharmacologic properties, such as antioxidant, antiinflammatory, and antifibrotic properties. It is important to note that not all the analogs are the same, and their stability and efficacy are dose-dependent and related to a specific type [15][16][17].…”
Section: Curcumin (Curcuma Longa)mentioning
confidence: 99%
“…The turmeric-derived polyphenol curcumin has been tested for therapeutic potential against SARS-CoV-2 (based on potential anti-HIV activity due to HIV-1 or HIV-2 protease inhibitor and HIV-1 integrase inhibitor activities, possible inhibition of SARS-CoV-2 has been suggested). It has also been shown that Zika and chikungunya virus incubated with curcumin lose their infectivity [16]. The potential mechanism of action relies on the reduction of the protein level of the Ang II type 1 (AT1) receptor and upregulation of the Ang II type 2 (AT2) receptor, evidenced by an increased ratio of AT2 receptor to AT1 receptor in the curcumin group (1.2 ± 0.02%) vs. the Ang II group (0.7 ± 0.03%, p = 0.05).…”
Section: Curcumin (Curcuma Longa)mentioning
confidence: 99%
“…Sheng Mai Injection, Gong Niu Huang Pill, Shen Mai Injection, Shen Fu Injection, and a Su He Xiang Pill are also used in patients in critical condition. Some other medicinal herbs suggesting to test in order to prevent and treatment of COVID-19 are dried rhizome of Curcuma longa L. This herb has antiviral activities against herpes simplex virus and HIV, therefore, it can also have inhibitory effects in terms of SARS-CoV-2 entry into the host cell (125).…”
Section: Effective Natural Herbsmentioning
confidence: 99%